2017
DOI: 10.1039/c6an02693a
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid plasmonic–photonic whispering gallery mode resonators for sensing: a critical review

Abstract: In this review we present the state of the art and the most recent advances in the field of optical sensing with hybrid plasmonic–photonic whispering gallery mode (WGM) resonators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 135 publications
0
51
0
Order By: Relevance
“…Recently, several groups including our own suggested that hybrid plasmonic-dielectric resonators can be constructed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], raising the idea that exactly this trade-off between confinement and Q can be reached. In this work we present a survey of the performance that should be available with hybrids if one assumes access to state-ofthe-art building block cavities and antennas.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups including our own suggested that hybrid plasmonic-dielectric resonators can be constructed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], raising the idea that exactly this trade-off between confinement and Q can be reached. In this work we present a survey of the performance that should be available with hybrids if one assumes access to state-ofthe-art building block cavities and antennas.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the detection resolution, we use a commonly accepted criterion that shifts of 1/100 of the linewidth can be detected with an adequate signal-to-noise ratio [31,[33][34][35], and obtain the resolution of our sensor to be 0.16% RH, which is better than typical microfiber [9,31,[36][37][38][39] or metallic nanoparticle [40,41] based humidity sensors.…”
Section: Single-cavity-based Optical Rh Sensormentioning
confidence: 99%
“…Hybrid microcavities have been reported to utilize the plasmon resonances to further enhance the light–matter interaction [ 85 , 86 , 87 , 88 , 89 ]. Advanced signal processing techniques such as self-reference differential detection, frequency locking (or phase locking detection) are developed to improve the signal and noise ratio (SNR) [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Optofluidic Microcavities For Biosensorsmentioning
confidence: 99%